Tahapan Pemecahan Masalah dengan Diagram Bar pada Soal Cerita - Wiworo Wiworo (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2021)
Word problems are still one of the causes of students' difficulties in learning mathematics. The four stages of problem solving suggested by Polya are: (1) understanding the problem, (2) planning a strategy, (3) implementing the strategy, and (4) checking and interpreting the results. One of the strategies to solve word problems that can be applied is by making diagram. The bar diagram model is a form of visual representation that can help students to solve word problems. The use of bar diagram in solving word problems can be a strategy for students to bridge the transition from understanding problems and making mathematical expressions. The process of creating a bar diagram model represents a visualization of known and unknown information and helps to identify how this information can be used to solve the problems. This paper discusses problem solving stages using bar diagram to solve word problems.